2018
DOI: 10.1038/s41426-018-0096-z
|View full text |Cite
|
Sign up to set email alerts
|

ZIKA virus infection causes persistent chorioretinal lesions

Abstract: Zika-infected patients can have eye involvement ranging from mild conjunctivitis to severe chorioretinal lesions, however the possible long-term sequelae of infection and timeline to recovery remain unknown. Here we describe the partial recovery of chorioretinal lesions in an immunocompetent patient diagnosed with bilateral posterior uveitis associated with Zika infection and show that some lesions resolved with focal atrophy evident as pigmentary changes on funduscopy. To better understand the progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 37 publications
5
72
0
Order By: Relevance
“…Other factors to consider for future testing are the interactions between the developmental stage and/or tissue type of infected cells and the baseline ADAR editing level, as well as the presence/absence of potential ADAR editing targets. For example, one can evaluate whether ocular damage is associated with dysregulation of developmentally important ADAR editing of Gabra3 in the retina, among other ADAR targets. Comparisons of the distribution and expression of edited and unedited isoforms at both the transcript and protein levels will be critical in such experiments.…”
Section: Testing the New Hypothesismentioning
confidence: 99%
“…Other factors to consider for future testing are the interactions between the developmental stage and/or tissue type of infected cells and the baseline ADAR editing level, as well as the presence/absence of potential ADAR editing targets. For example, one can evaluate whether ocular damage is associated with dysregulation of developmentally important ADAR editing of Gabra3 in the retina, among other ADAR targets. Comparisons of the distribution and expression of edited and unedited isoforms at both the transcript and protein levels will be critical in such experiments.…”
Section: Testing the New Hypothesismentioning
confidence: 99%
“…To study the effect of systemic ZIKV infection on ocular tissue, pups of immune‐competent C57BL/6 WT mice (B6wt) were subcutaneously inoculated with the ZIKV strain PRVABC59, 1‐day post birth . ZIKV RNA was detectable in the eye; 3 dpi and the virus persisted in the eye tissues after being rapidly cleared from the peripheral circulation.…”
Section: Pathophysiologymentioning
confidence: 99%
“…These patients displayed pigmented outer retinal lesions and hyper‐reflective elevations of the outer retina and loss of ellipsoid layer . Studies in mice further suggested that the neuronal cell components in the cornea and retina were more susceptible than the rod and cone photoreceptor cells to the viral onslaught . It is hypothesized that the retinal compartment of the eye could be breached by ZIKV infection of the outer layer of the BRB, ie, the retinal pigment epithelial cells or by infection of the retinal vascular endothelial cells, which constitute the inner layer of BRB …”
Section: Pathophysiologymentioning
confidence: 99%
“…Their recruitment in an infected tissue is a host-defence mechanism that can induce tissue damage if not finely regulated. Infection of neonatal C57BL/6 wild-type mice at 1 day post birth with ZIKV showed that the virus infects the cornea and retina resulting in chorioretinal lesions (86). The infection is followed by inflammatory cells infiltration and increased local expression of chemokines.…”
Section: Moreover Mpo Was Released By Neutrophils Collected From Micmentioning
confidence: 99%